Investigating on crystal structure, thermodynamic, and molecular dynamic of lead-free organic-inorganic hybrid [NH3(CH2)2NH3]ZnBr4 crystals. (1st May 2023) - Lim, Ae Ran; Jeon, Hara
Abstract: In this study, lead-free organic-inorganic hybrid [NH3 (CH2 )2 NH3 ]ZnBr4 crystals were grown by slow evaporation and analyzed. The crystals showed orthorhombic structure with the P 21 21 21 space group, and the following lattice constants: a = 8.3818 (2) Å, b = 10.8880 (4) Å, c = 11.8175 (4) Å, and Z = 4. The crystals were stable up to 584 K, with two phase transitions at 468 K (TC1 ) and 503 K (TC2 ), as indicated by differential scanning calorimetry and differential thermal analysis. The structural environments of the atoms were analyzed by 1 H and 13 C NMR. On increasing the temperature, the spin-lattice relaxation time, T1ρ, decreased rapidly due to large energy transfer at high temperatures, as indicated by large thermal displacements of the 1 H and 13 C atoms of the cation. Additionally, the activation energy, Ea, at high and low temperatures was found to be 49.23 and 1.44 kJ/mol, respectively, for the molecular motion of 1 H, and 37.93 and 2.13 kJ/mol, respectively, for that of 13 C. Analyzing the physiochemical properties of [NH3 (CH2 )2 NH3 ]ZnBr4 could facilitate its application in stable and environment-friendly solar cells. Highlights: Crystal structure of [NH3(CH2)2NH3]ZnBr4. Thermodynamic property. Phase transition temperature. Molecular motion. Application of organic-inorganic hybrid.